Artificial Intelligence (AI)-Powered Chest X-Ray Enables Early-Stage Lung Cancer Diagnosis in a Patient Presenting with Acute Coronary Syndrome: Role for AI in Incidental Screening - Laksmi Wulandari; Fierly Hayati; Santhosh Shivabasappa (http://dharmais.co.id/, 2026)
Introduction: Lung cancer is the most common cause of cancer-related death worldwide. Screening with low-dose computed tomography (LDCT) of the thorax is recommended for high-risk individuals. However, its utilization is limited in many developing countries because of cost and accessibility. Chest X-ray is a commonly used imaging test for the initial evaluation of patients with chest pain. But nodules are frequently missed, and recent advances in artificial intelligence software have shown potential in identifying subtle nodules. There are limited reports on the real-world impact of AI chest X-ray on lung cancer detection.Case Presentation: A 53-year-old male who presented with chest pain and shortness of breath to the cardiology clinic. The patient was diagnosed with non-ST elevation acute coronary syndrome (NSTEACS) and managed appropriately. Artificial intelligence (AI)-enabled chest X-ray identified a high-risk nodule in the right lower zone that was suspicious for malignancy. Subsequent contrast chest computerized tomography scan revealed an enhancing solid lesion with a spiculated margin in the right lower lobe, and the biopsy result confirmed lung adenocarcinoma (stage IB). The patient underwent right inferior lobectomy and is doing well.Conclusions: This case report highlights the potential of AI chest X-ray for the incidental detection of suspicious nodules in patients presenting with non-pulmonary symptoms. In settings with no established lung cancer screening programs, integration of AI in the routine chest X-ray workflow can help detect high-risk pulmonary nodules and facilitate early diagnosis of lung cancer.